The Urgency of Disability Service Units in Higher Education as an Effort to Realize Inclusive Access to Higher Education - Mariska, Refi; Aulia, Dine Mega; Septiana, Fajar Indra (Angstrom Centre of Education, 2024)
This research is based on the gap between theory, regulation and implementation of the fulfillment of rights for students with disabilities in higher education based on Law No. 8 of 2016. One of the important issues of rights fulfillment in the Law is the right to education in higher education. Explicitly, the law mentions several obligations of universities, public and private, to play an active role in fulfilling and promoting the rights of persons with disabilities. In this literature study, we aim to study in depth the implementation of each policy and advocacy for the rights of students with disabilities carried out by several universities in Indonesia with the formation of disability service units that have a role in pursuing good practices to realize inclusive universities. Based on the results of the research, the disability service unit is one of the efforts to realize inclusive universities and become a forum for fulfilling the rights of students with disabilities to obtain the right to education, which includes the rights of persons with disabilities, fulfillment of equal opportunities for persons with disabilities, respect, protection and fulfillment of the rights of persons with disabilities, including the provision of accessibility and proper accommodation.